Neonatal Colibacillosis in Calves - HAMED, O.; El-GUSBI, B. H. M.; NOUR, A. M. (The Libyan Journal of Agriculture, 2023)
The cause of diarrhoeal disease in calves was investigated in 40 Holstien Fiensian calves in Sidi El-Misri Cattle Raising Station, Tripoli, Libyan Jamahiriya. Five Hundred and Forty Six rectal swabs were collected from these animals for bacteriological examination. Escherichia coli was found to be the main cause of diarrhoea and was isolated from 42.12% of the collected swabs. Klebsiella organisms were also isolated at a rate of 2.19%. 10% of calves died from diarrhoea.